Awareness and application of infection control recommendations in the private practice of Iraqi dentists (Mustansiria Dental Journal, 2024)
Infection control rules are extremely important in dental office because dangerous infections can be passed on to the dental health workers or the patient during treatment, the aim of this study was to assess the awareness and knowledge of  a group of Iraqi dentists regarding application of infection control rules in their private practice , data was collected by an interview with the study group (35 dentists) to fill a questionnaire. Results showed that many of the infection control measures were inadequately applied, leading to a conclusion that training in both educational and practical fields is required to improve the knowledge related to infection control measures.